Comparing Predictability of SRK/T, Barrett Universal II, and Kane Formulas on High Myopia Phacoemulsification - Ryamizard, Rizal; Wisnu Sadasih; A. Rizal Fanany; Fatimah Dyah Nur Astuti (Majalah Oftalmologi Indonesia, 2026)
Introduction: The refractive outcomes of phacoemulsification surgery have improved significantly in recent years, but it is still challenging to obtain good outcomes in eyes with long axial lengths. This study compares the difference between the predicted and manifest refraction outcomes between Sanders Retzlaff Kraff theoretical (SRK/T), Barrett Universal II (BU-II), and Kane formula in high myopia patients undergoing uncomplicated phacoemulsification surgery. Methods: This cross-sectional design study includes eyes with high myopia (axial length ≥26.0 mm) that undergo uncomplicated phacoemulsification surgery with intraocular lens implantation between January 2024 and January 2025 at Semarang Tertiary Hospital. The one-month post-surgery mean absolute prediction errors (MAE) difference between SRK/T, BU-II, and Kane formula are calculated and analyzed using the Wilcoxon Sign Rank Test. Result: Thirty-seven eyes meeting the criteria were analyzed, with a mean axial length of 29.07±2.42 mm. The MAE and percentages of eyes within 0.50 diopters (D) refractive prediction errors of the three formulas are as follows: SRK/T (0.68 D, 60%), BU-II (0.41 D, 73%), and Kane (0.37 D, 76%). There is a statistically significant difference in MAE between SRK/T vs BU-II (p < 0.05) and SRK/T vs Kane (p < 0.05). Conclusion: The Kane and BU-II formula has better accuracy in predicting refractive outcome (lower MAE and higher percentages of eyes within 0.5 D refractive prediction errors) than the SRK/T formula in patients with high myopia who undergo uncomplicated phacoemulsification surgery.